A novel lie detection method based on extreme learning machine using P300 - Xiong, Yijun; Yang, Yong; Gao, Junfeng (ICISCE 2012 : IET International Conference on Information Science and Control Engineering 2012 : 7-9 December 2012, 2012)
Machine learning-based lie detection has drawn much attention recently. In this paper, we used extreme learning machine (ELM), a recently-proposed machine learning method based on a single layer feedforward network (SLFN), to classify P300 potentials from guilty subject and non-P300 potentials from innocent subject. Back-propagation network and support vector machine classifiers were also used to compare with the proposed method. The number of hidden nodes in ELM was tuned using training with the 10-fold cross validation. The experimental results show that the proposed method reaches the highest classification accuracy with extremely less training and testing time, compared with the other classification models.